2017
DOI: 10.1128/mbio.02273-16
|View full text |Cite
|
Sign up to set email alerts
|

Negative Autogenous Control of the Master Type III Secretion System Regulator HrpL inPseudomonas syringae

Abstract: The type III secretion system (T3SS) is a principal virulence determinant of the model bacterial plant pathogen Pseudomonas syringae. T3SS effector proteins inhibit plant defense signaling pathways in susceptible hosts and elicit evolved immunity in resistant plants. The extracytoplasmic function sigma factor HrpL coordinates the expression of most T3SS genes. Transcription of hrpL is dependent on sigma-54 and the codependent enhancer binding proteins HrpR and HrpS for hrpL promoter activation. hrpL is oriente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 62 publications
5
24
0
Order By: Relevance
“…A recent study revealed that HrpL imposes autogenous control via the shared intergenic region with hrpJ , whose promoter is indispensable for this effect (Fig. B, process 1 and Table ) (Waite et al ., ). By forming an hrpJ promoter‐RNA polymerase‐HrpL complex, the putative HrpRS‐binding element and integration host factor recognition elements in the hrpL promoter are occluded, thus generating negative control of hrpL transcription (Waite et al ., ).…”
Section: Induction Of Alternative Sigma Factor Hrpl Is Predominantly mentioning
confidence: 97%
See 2 more Smart Citations
“…A recent study revealed that HrpL imposes autogenous control via the shared intergenic region with hrpJ , whose promoter is indispensable for this effect (Fig. B, process 1 and Table ) (Waite et al ., ). By forming an hrpJ promoter‐RNA polymerase‐HrpL complex, the putative HrpRS‐binding element and integration host factor recognition elements in the hrpL promoter are occluded, thus generating negative control of hrpL transcription (Waite et al ., ).…”
Section: Induction Of Alternative Sigma Factor Hrpl Is Predominantly mentioning
confidence: 97%
“…B, process 1 and Table ) (Waite et al ., ). By forming an hrpJ promoter‐RNA polymerase‐HrpL complex, the putative HrpRS‐binding element and integration host factor recognition elements in the hrpL promoter are occluded, thus generating negative control of hrpL transcription (Waite et al ., ). This feedback control can help to minimize the activation of plant immune systems and allow the pathogen to evade host recognition (Waite et al ., ).…”
Section: Induction Of Alternative Sigma Factor Hrpl Is Predominantly mentioning
confidence: 97%
See 1 more Smart Citation
“…The GacSA two‐component system is required for hrpL , rpoN and hrpR‐hrpS expression (Chatterjee et al ., ), although how plant signals are perceived and transduced into the Hrp regulatory network remains still poorly understood. Importantly, σ HrpL negatively regulates its own transcription (Waite et al , ), which is not a common feature of Pseudomonas σ ECF factors which usually promote their own expression (Chevalier et al , ). It has been proposed that this negative feedback on σ HrpL activity may fine‐tune T3SS production to minimize the elicitation of plant defenses (Waite et al , ).…”
Section: P Syringae σHrpl Factormentioning
confidence: 99%
“…Importantly, σ HrpL negatively regulates its own transcription (Waite et al , ), which is not a common feature of Pseudomonas σ ECF factors which usually promote their own expression (Chevalier et al , ). It has been proposed that this negative feedback on σ HrpL activity may fine‐tune T3SS production to minimize the elicitation of plant defenses (Waite et al , ).…”
Section: P Syringae σHrpl Factormentioning
confidence: 99%